Investigating Relationship between Positive Organizational Behaviors and Organizational Commitment among Nurses at Emam Khomeyni Hospital in Jiroft, Iran, in 2017: A cross Sectional Study - Saadat Salari1, Fereshteh Daneshi2, Motahare Pilevarzadeh1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: One of the most important indicators of development and excellence of an organization is the presence of committed and loyal manpower. Thus, this study aims to investigate the relationship between positive organizational behaviors and organizational commitment among nurses working at Emam Khomeyni Hospital of Jiroft, Iran in 2017.Method: This study is correlative-descriptive. The statistical population consisted of all the nurses working at Jiroft Hospital and they were all selected as samples. The data were analyzed using SPSS v25. Independent t-tests were applied to investigate the relationships between demographic specifications, organizational behavior, and organizational commitment, while correlation coefficient was employed to study the relationship between the main variables and Regression test and Pearson Correlation Coefficient were used to examine the relationship between organizational commitment and organizational behaviors and its dimensions.Results: the results indicated that there was an inverse and significant relationship between organizational behavior and organizational commitment in general (p<0.001) and in emotional dimension (p<0.001) and normative dimension (p<0.01) in particular. Moreover, a positive and significant relationship was observed between positive organizational behavior and organizational commitment (p=0.03).Conclusion: since positive behaviors are of great importance for performance evaluation systems among nurses and, at the same time, can affect a variety of their attitudes, including organizational commitment, it is suggested to improve nurses’ understanding of positive organizational behavior and organizational commitment to allow them to have better opportunities to better provide services in their workplace.